Bahasa Tabu di Ruang Publik: Melihat Pesan dalam Film Mlekoki (Sutasoma : Jurnal Sastra Jawa, 2022)
Taboo language, which is usually used in private spaces, is often found in public spaces and is favored by various groups. This condition is reflected in the short film Mlekoki Official, which gets a lot of enthusiasm from Youtube viewers. The aims of this study are to find a benchmark for the public to feel like taboo language in public spaces and find the factors that cause the public to feel like taboo language in public spaces. This research method uses descriptive research and a qualitative approach. The data source of this research is a secondary data source from Mlekoki Official. Data collection techniques using observation and literature study. Data validity by triangulation and data analysis by interactive models. The results of this study conclude that the short film Mlekoki Official, which contains a lot of taboo language, is liked by the public. This can be seen from the large number of viewers and likes. The factors that cause the liking for the Mlekoki Official short film are because (1) it is not common among the public (judging by the theme raised); (2) a lot of taboo language (language that is rarely used in public spaces); and (3) raising the theme of general social problems (problems that are often experienced by the surrounding community) Keywords: taboo language; youtube; banyumasan